Antibacterial activity of leaves and flowers of Clitoria ternatea (butterfly pea plant) in Sri Lanka by using different solvent extracts - T. D. Senarathna; H. Mudalige; S. Dias (Sri Lankan Journal of Infectious Diseases, 2021)
NAA